Relationship Between Location of Project and Height of Building Toward Health and Safety Cost in Rusunawa Construction Projects - Amalia Dwi Purnamasari; Ratih Fitriani; Yusuf Latief (Journal of International Conference Proceedings (JICP), 2021)
The rise of separatist actions in various regions in Indonesia raises concerns for all parties, including contractors as providers of construction project services. Not only separatism, thuggery acts that occur in the construction project environment are also considered to be 'natural'. The current SMK3 cost planning does not take into account events in different project locations, particularly in the western, central, and eastern parts of Indonesia. This should be considered since each region in Indonesia has different climatic conditions and characteristics. This study focuses on analyzing the relationship between project location and building height on K3 cost and further reviews the factors in these variables which are the dominant influence on K3 cost. The purpose of this study is to analyze the factors in each variable that affect K3 costs and analyze the relationship between project location variables and building heights on the K3 cost model in Rusunawa construction projects. This study analyzes data from 5 experts and 12 respondents who work in construction companies using quantitative methods and questionnaires. The results of the study indicate that there are 5 variables with 33 indicators that affect the K3 cost of the Rusunawa construction project.